Effects of hip adductor exertion on EMG activity of the vastus medialis oblique (VMO) and vastus lateralis (VL) DJlUscleds uring: squat exercise - Sirirat Kaewwichai (2013)
11th National Grad Research Conference. Graduate School,Valaya Alongkorn Rajabhat University,Pathum Thani, Thailand. Page 283-292